Steel Slag and Limestone as a Rock Filter for Eliminating Phosphorus from Domestic Wastewater: A Pilot Study in a Warm Climate - Maarup, Syahrul Nizam; Hamdan, Rafidah; Othman, Norzila; Al-Gheethi, Adel; Alkhadher, Sadeq; El-Hady, M. M. Abd; Saeed, S. El-Sayed (Mdpi, 2023)
Phosphorus input with excessive use of fertilizers and manure as one of the main sources of nutrient pollution has increased recently in the wastewater as result of intensive farming and industrialized and densely populated areas. The novelty of the current work lies in improving a Vertical Aerated Rock Filter (VARF) using steel slag and limestone media to enhance the efficiency of a rock filter (RF) to eliminate total phosphorus (TP) from domestic wastewater. RF was designed with steel slag and limestone (calcium hydroxide) as a pilot scale called vertical aerated steel slag filter (VASSF) and optimized based on hydraulic loading rates (HLR) (0.16 to 5.44 m3/m3 day) and airflow rates ranging from 3 to 10 L/min. The highest removal for the design of the laboratory scale steel slag filter (LSSSF) was achieved by approximately 58%, while for the laboratory-scale limestone filter (LSLSF), it was 64%. The VASSF achieved a removal percentage at 30% of TP, biological oxygen demand (BOD; 89%), chemical oxygen demand (COD; 75%), total suspended solids (TSS; 73%), and total coliforms (TC; 96%), recorded with 7 L/min of an airflow rate and 1.04 m3/m3 day of hydraulic loading rate (HLR) at potential of hydrogen (pH) 7.3 and 5.09 mg/L of dissolved oxygen (DO). These findings indicated that the steel slag is higher than limestone in TP removal, because of ion exchange between phosphorus hydrolysis and the adsorption process. Moreover, in the pilot study, the removal efficiency needs more investigation to determine the best conditions for TP considering the temperature, which is unstable, and presence of other pollutants, which might negatively affect the removal efficiency under unstable conditions